Theoretical investigation of Ti and Ni co-doping on the anti-disproportionation ability of ZrCo alloy. (22nd August 2018) - Yang, Guo; Liu, Wenguan; Wu, Shengwei; Wu, Xijun; Qian, Nan; Cheng, Hongwei; Gao, Jie; Zeng, Youshi; Liu, Wei; Li, Yan
Abstract: First-principles calculations are utilized to investigate the effect of Ti and Ni co-doping on the anti-disproportionation ability of ZrCo alloy. In Ti and Ni co-doped ZrCoH3, the Ti-H(8e) bond shows a strong ionic feature and the Ni-H(8e) bond exhibits covalent bonding characteristic. Judged by the Zr-H(8e) bond length, the size of the 8e site and H diffusion barrier out of the 8e site in ZrCoH3, it can be concluded that the Ti + Ni co-doping can impair the anti-disproportionation ability of Ti doping in ZrCo alloy, which uncovers the mechanism of the negative effect of Ni on the Ti-doped ZrCo alloy found in the previous experimental results.